Digital Debt – The Breach with Unpredictable Effects in the Management of the Accounting Expertise Office - Luana COSĂCESCU (CECCAR Business Review)

(untitled)
Based on their solid professional training, as well as their vocation, the expert accountant has a special sense of organizing and managing his workplace and optimizing the cost-benefit ratio for the information resources and channels used, including digital ones. However, we cannot completely exclude the possibility of some unpleasant manifestations of digital debt in the accounting expertise office, with numerous negative consequences. Thus, at some point, an informational pressure from the outside but also for the outside can make its presence felt on the flow of digital channels (which will have a lot of disruptions, oversaturation, even functional blockages). The pressure, manifesting as an avalanche difficult to manage, will influence to a greater or lesser extent the emergence of the phenomenon of digital debt. The latter ends up generating “digital inflation” over time, that is, the information packages entered, processed, stored, archived, or distributed will no longer align with the office’s performance indicators. Under these circumstances, the accountant must demonstrate a certain level of digital maturity to notice which of the influencing factors of the increase in digital debt (procrastination, digital noise, multitasking or lack of focused work) makes its presence felt and acts as a breach with an unpredictable effect in the management of the accounting expertise office.